Actualization of gifted schoolchildren’s intentional experience in the process of mastering geometric concepts: from support to activity mechanism - Natalia Georgievna Podaeva (Universidade Estadual Paulista, 2021)
People’s intellectual abilities become a powerful civilization resource. Therefore, intellectually gifted schoolchildren’s development should be the focus of the state educational policy. Russian opinion leaders interpret the phenomenon of giftedness as a systemic quality that describes the child’s psyche as a whole. Such an approach turns into a priority to update and enrich the gifted schoolchildren’s intentional experience during geometry teaching. It assumes the development of a particular subjective state of orientation and selectivity of individual cognitive activity in preferences. This unique state becomes a mental activity mechanism, not just an accessory. The statistical data analysis confirms the hypothesis: the efficiency of actualizing gifted schoolchildren’s intentional experience in the form of their individual dispositions, beliefs, and emotional assessments while solving geometric problems during academic competitions is provided by specifically organized educational activities. It positively correlates with the level of mental activity development during mastering the activity methods with geometric concepts.